Alcohol-Related Elevation of Liver Transaminase Is Associated With Gut Microbiota in Male - Jiao, Mengfan; Yan, Su; Shi, Qingmiao; Liu, Ying; Li, Yaoguang; Lv, Jun; Ding, Suying; Li, Ang (Frontiers in Medicine, 2022)
Alcoholic liver damage has become a widespread health problem as alcohol consumption increases and is usually identified by elevated liver transaminase. We conducted this study to investigate the role of gut microbiome in the individual susceptibility to alcoholic liver injury. We divided the participants into four groups based on alcohol consumption and liver transaminase elevation, which were drinking case group, drinking control group, non-drinking case group, and non-drinking control group. Drinking case group meant participants who were alcohol consumers with elevated liver transaminase. We found that alpha and beta diversities of the drinking case group differed from the other three groups. Species Faecalibacterium prausnitzii and Roseburia hominis were significantly in lower abundance in drinking case group and were proved the protective effect against inflammatory liver damage in the former study. Ruminococcus gnavus exhibited the most positive association to ALT and aspartate aminotransferase (AST) and contributed to liver inflammation.